Thematic Learning Model of Science, Environment, Technology and society in Improving Elementary Students’ Science Literacy - Atmojo, Setyo Eko; Kurniawati, Wahyu (JPI (Jurnal Pendidikan Indonesia), 2018)
The purpose of this research was to develop a science thematic model of science, environment, technology and its validity so that it can be used to improve the literacy of science of elementary school students. This was a research and development. The data collected in this research consisted of model validity data, students’ science literacy, students’ activity, students’ and teachers’ response to the developed learning model. The data collection techniques used was questionnaires, observations and tests. The data were analyzed by descriptive analysis. The result of the research showed that the developed thematic learning model of science, environment, technology and societies got an average score of 4.11 falling into the valid category. The ability of science literacy increased from the previous 41.71 at a very low level (<54) to 62.91 at a moderate level (60-75). The average score of student activity during the learning was in a good category. Students’ and teachers’ responses to the developed learning model were positive.